2023
DOI: 10.5603/ahp.a2023.0004
|View full text |Cite
|
Sign up to set email alerts
|

Letermovir use in children after hematopoietic cell transplantation: summary of reported data

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Еще одну проблему для реципиентов ТГСК детского возраста представляют ограничения к назначению противовирусных препаратов детям [18]. Так, доказавший свою эффективность в качестве профилактики и превентивной терапии ЦМВ-инфекции у взрослых летермовир может применяться у детей только «off-label», однако клинические исследования демонстрируют его безопасность и эффективность у детей [19].…”
Section: Introductionunclassified
“…Еще одну проблему для реципиентов ТГСК детского возраста представляют ограничения к назначению противовирусных препаратов детям [18]. Так, доказавший свою эффективность в качестве профилактики и превентивной терапии ЦМВ-инфекции у взрослых летермовир может применяться у детей только «off-label», однако клинические исследования демонстрируют его безопасность и эффективность у детей [19].…”
Section: Introductionunclassified
“…3 Apart from Chen et al study, 1 between 2019 and 2023 total 11 papers were published on use of letermovir in prophylaxis in pediatric patients after HCT, including overall 64 patients. [4][5][6][7][8][9][10][11][12][13][14] In updated summary of these reported cases, 15 clinically significant CMV infection has occurred only in two of 64 (3.1%) patients. This is much lower than in the pivotal adult study (7.7% at week 14, and 37.5% at week 24) 2 and in Chen et al study (9.8% at day +180).…”
mentioning
confidence: 96%
“…Progress is still being maintained. Recent trials have shown the safety and efficacy of letermovir use for prolonged (200 days) prophylaxis, and also in other patient populations such as children, as well as in secondary prophylaxis [10].…”
mentioning
confidence: 99%